The Efforts to Prevent Money Laundering in Indonesia - Haq, Muhammad Alhadi; Bakir, Herman; Redi, Ahmad (CV. Publikasi Indonesia, 2023)
Due to its criminal nature, money laundering by transnational organized criminal groups will negatively impact the country's micro and macro economies. These impacts can disrupt the functioning of the market mechanism, create distortions that disrupt economic efficiency and the distribution of income and wealth in society and disrupt national development. The crook demonstration of tax evasion is an interaction or action that expects to stow away or mask the beginning of cash and resources got from criminal demonstrations which are then changed over into resources that seem to start from genuine exercises. Corruption, bribery, goods/labor/immigrant smuggling, banking, narcotics, psychotropic, trafficking, kidnapping, terrorism, theft, embezzlement, and fraud are all criminal acts that can lead to money laundering. The stages in the crime of money laundering are Placement, Layering, and Integration. The legal instrument for money laundering is Article 3 of RI Law No. 8 of 2010 concerning Money Laundering. And the way to deal with money laundering in Indonesia is to postpone transactions on assets originating from criminal acts. Furthermore, it did the blocking of criminal act assets and suspended transactions related to money laundering crimes.